1999
DOI: 10.1038/sj.bjc.6690627
|View full text |Cite
|
Sign up to set email alerts
|

Induction with mitomycin C, doxorubicin, cisplatin and maintenance with weekly 5-fluorouracil, leucovorin for treatment of metastatic nasopharyngeal carcinoma: a phase II study

Abstract: The combination of cisplatin and 5-fluorouracil (5-FU) (PF) is the most popular regimen for treating metastatic nasopharyngeal carcinoma (NPC) but it is limited by severe stomatitis and chronic cisplatin-related toxicity. A novel approach including induction with mitomycin C, doxorubicin and cisplatin (MAP) and subsequent maintenance with weekly 5-FU and leucovorin (FL) were designed with an aim to reduce acute and chronic toxicity of PF. Thirty-two patients of NPC with measurable metastatic lesions in the liv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 24 publications
1
22
0
Order By: Relevance
“…However, as Cohort 2 was used for validation of the score and all the patients in Cohort 2 were treated, we elected to reanalyse Cohort 1 to restrict the derivation of a new prognostic index score to only patients given chemotherapy. The reason for the reanalysis is that chemotherapy has an impact on survival outcome in patients with disseminated NPC, although there are no randomised comparison studies between chemotherapy and best supportive care (Fandi et al, 1994;Hong et al, 1999). This is also supported by the fact that incorporation of chemotherapy in locally advanced disease has been shown to improve progression-free and overall survival Cohort 1 Figure 1 Survival curves for Cohorts 1 and 2.…”
Section: Discussionmentioning
confidence: 99%
“…However, as Cohort 2 was used for validation of the score and all the patients in Cohort 2 were treated, we elected to reanalyse Cohort 1 to restrict the derivation of a new prognostic index score to only patients given chemotherapy. The reason for the reanalysis is that chemotherapy has an impact on survival outcome in patients with disseminated NPC, although there are no randomised comparison studies between chemotherapy and best supportive care (Fandi et al, 1994;Hong et al, 1999). This is also supported by the fact that incorporation of chemotherapy in locally advanced disease has been shown to improve progression-free and overall survival Cohort 1 Figure 1 Survival curves for Cohorts 1 and 2.…”
Section: Discussionmentioning
confidence: 99%
“…Among them, 34 patients had received cisplatin-containing regimens including PF (7 cases) and MAP-FL (28 cases). MAP-FL, which also contained doxorubicin, was the regimen of a phase II clinical trial conducted at our institute [7]. Details of the chemotherapy regimen are listed in table 2.…”
Section: Resultsmentioning
confidence: 99%
“…The 2-year survival rate of patients with advanced NPC is around 10% [2, 3, 5, 6, 7, 8]. Many of these patients, although initially responsive to chemotherapy, do not enjoy a durable remission.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fluoropyrimidines are thought to also function as angiogenesis inhibitors 96. Results from studies in Taiwan97 and Singapore98 have shown great promise in terms of median survival rates in metastatic NPC. The use of biomarkers has provided new possibilities for tailoring treatments for patients who are most likely to benefit.…”
Section: Primary Treatment Of Npcmentioning
confidence: 99%